2003
DOI: 10.1016/s0022-5223(03)00749-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation in patients subjected to coronary artery bypass grafting

Abstract: Postcoronary artery bypass grafting atrial fibrillation is associated with more complicated postoperative outcome. Higher preoperative heart rate and postoperative pulmonary capillary wedge pressure were the independent predictors of atrial fibrillation. Recent unstable angina is not related to the occurrence of postcoronary artery bypass grafting atrial fibrillation. Ischemic preconditioning significantly suppresses postcoronary artery bypass grafting atrial fibrillation, suggesting that ischemic precondition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
4
26
0
9
Order By: Relevance
“…29, 30 Wu et al reported that higher PCWP on POD1 was an independent predictor of POAF (11.4±2.3 vs. 10.7±2.7 mmHg, P=0.047). 31 Frost et al noted that CVP on admission to the ICU in the POAF group was 2 mmHg higher than that in the group without POAF. 32 These differences in PCWP and CVP were statistically significant, but in the clinical setting they should be carefully monitored because the actual differences were small.…”
Section: Discussionmentioning
confidence: 97%
“…29, 30 Wu et al reported that higher PCWP on POD1 was an independent predictor of POAF (11.4±2.3 vs. 10.7±2.7 mmHg, P=0.047). 31 Frost et al noted that CVP on admission to the ICU in the POAF group was 2 mmHg higher than that in the group without POAF. 32 These differences in PCWP and CVP were statistically significant, but in the clinical setting they should be carefully monitored because the actual differences were small.…”
Section: Discussionmentioning
confidence: 97%
“…The recognition of risk factors for the occurrence of postoperative AF is of paramount importance for the adoption of prophylactic and therapeutic measures for these patients, with a view to reducing rates of heart failure, kidney failure, pneumonia, prolonged mechanical ventilation, cerebrovascular accident and early and late deaths [7][8][9][10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of beta blockers preoperatively is considered an effective measure in the prophylaxis of this arrhythmia 10,11,14,24 .…”
mentioning
confidence: 99%
“…1) The presence of AF following CABG is associated with a two-fold increase in cardiovascular morbidity and mortality. 2) There is a higher occurrence of heart failure and stroke, both related to longer hospital stay, and consequently, with very high surgery costs. 3) The underlying mechanisms that lead to onset and persistence of arrhythmia have been diffi cult to elucidate.…”
Section: Introductionmentioning
confidence: 99%